The Instructional Management on Soft Skills in Islamic Perspective: A Multi-Case Study at Sekolah Karakter Indonesia Heritage Foundation (IHF) and Brawijaya Smart School (BSS) - Aries Musnandar (Khatulistiwa, 2020)
The finding result of Alfred Binnet dan Theodore Simon (1905) about IQ (Intelligence Quotient) is perceived by many people as a determined factor of an individual success in various life sectors. Therefore, the emphasizing on academic activities in schools including elementary schools is based on intellect/IQ and hard skills over soft skills. However, IQ and / or intellect approach has not succeeded yet in improving a student’s learning achievement in academic performance results, hard skills, moreover soft skills. This research is aimed to understand deeply on the importance and the need of soft skills development in schools especially elementary school. The study employs qualitative research method with multiple case study design, in which a meaning making activity is underlined as the first objective of interpretive research in understanding social phenomena of education activities. The phenomena of soft skillsoccurs in real-life events andcurrent situation, as well as programs and activities. In this qualitative research method the researcher conducted three main activities such as in-depth interview, observation and to get relevant data collection in order to enrich and complete the previous obtained data. Based on findings, it is known substantively that students’ soft skills will not be developed if the instructional management focuses on academic. Besides, soft skills will enhance significantly students’ academic results, because soft skills will enable and improve students’ potentials to reach the best learning achievement. In Islamic perspective, the quality of soft skills within akhlak-adab domain will be more better if soft skills’ development are referred to a sound heart (qolbun salim). Finally, it is shown in formal finding that the instructional management of students’ soft skills is a must and it is importance to be implemented in education particularly in elementary school.